Casta diva: La “venuta dal mare” nell’universo letterario di Cesare Pavese (TEST Ticontre. Theory Text Translation, 2022)
This article aims at investigating the background, the pretextual evolution, and the historical premises of the «woman from the sea» – «la venuta dal mare» – in imagery and works by Cesare Pavese. This enigmatic figure cooperates to the construction and conclusion of a literary tragedy, which develops over the years through texts of different regime, fictional or not fictional. The woman from the sea emerges, above all in Il mestiere di vivere, as the essential engine of a theatrical and melodramatic narrative machine, designed by a writer who yearns to self-represent as a maudit and proposes himself to the audience as epigone of Baudelaire.